Suppression of lupus nephritis and skin lesions in MRL/lpr mice by administration of the topoisomerase I inhibitor irinotecan - Keil, Andreas; Hall, Sean R.; Koerner, Meike; Herrmann, Martin; Schmid, Ralph A.; Frese, Steffen (Arthritis Research & Therapy, 2016)
Since the precise mechanism for the pathogenesis of systemic lupus erythematosus (SLE) is unknown, no targeted therapies in addition to immunosuppression are available so far. We recently demonstrated that administration of the topoisomerase I (topo I) inhibitor irinotecan at extremely low concentrations reversed established lupus nephritis in NZB/NZW mice. While profound immunosuppression was absent, we proposed changes in DNA relaxation and anti-double-stranded (ds)DNA antibody binding as the underlying mechanism. To exclude that these effects were restricted to NZB/NZW mice, irinotecan was used in a genetically different strain of lupus-prone mice.MRL/lpr mice were treated with high- and low-dose irinotecan beginning at 8 weeks of age. Treatment was repeated every fourth week. In vitro, DNA was relaxed by recombinant topo I, and altered anti-dsDNA antibody binding was measured by enzyme-linked immunosorbent assay.Administration of both high- and low-dose irinotecan prevented proteinuria and prolonged survival in MRL/lpr mice. Moreover, both concentrations of irinotecan significantly improved histopathology of the skin at 18 weeks of age. While only high-dose irinotecan diminished the numbers of plasmablasts and double-negative T cells, no changes in IgG-secreting cells or anti-dsDNA IgG were observed. In vitro, relaxation of DNA by topo I increased the binding of anti-dsDNA IgG but not the binding of anti-dsDNA IgM derived from the plasma of MRL/lpr mice.The beneficial effects of topo I inhibition in a second, genetically different strain of lupus-prone mice strongly implicate irinotecan as a new therapeutic option for human SLE.
EVALuna2:13356